A STUDY ON THE LEARNING APPROACH OF THE MALAYSIAN ADULT STUDENTS - Hee, Ong Choon (Journal of Technical Education and Training, 2014)
The purpose of this study is to identify the learning approach of the Malaysian adult students enrolled in continuing education. The non-experimental design method was used for the study and the 2-Factor Study Process Questionnaire was used for data collection on learning approaches. The questionnaire was found to be valid based on factor analysis and reliable in this study with reliability estimates of approximately r=.7 for both constructs using the Cronbach Alpha method. The sample consisted of 45 adult students who were enrolled in an Executive Diploma program in one public university in Malaysia. The findings of this study indicate that the adult students tend to adopt deep learning approach in their learning process. Test of significance on differences reveals that there are no significant group differences in the mean scores on deep learning approach regardless of gender, age group and work experience of respondents. It can be concluded that adult students tend to be deep learners rather than surface learners and education institutions need to take this into account their teaching and learning orientations to support adult students. For future research, this study offers validated measures of learning approach that can be used by future researchers in the similar research setting in Malaysia.